'Our Lincolnshire' : exploring public engagement with heritage - Lewis, Carenza (Access archaeology., 2019)
This work presents the aims, methods and outcomes of an innovative wide-ranging exploration of public attitudes to heritage, conducted in 2015-16 across Lincolnshire, England's second-largest county. As policy and practice evolve, this research will remain valuable as a snapshot in time of public engagement with heritage.